Memory Mates: An Evaluation of a Classroom-Based, Student-Focused Working Memory Intervention. Issue 2 (22nd December 2020) - Colmar, Susan; Double, Kit; Davis, Nash; Sheldon, Linda; Phillips, Natalie; Cheng, Matthew; Briddon, Sophie
Abstract: This applied experimental research tested the effectiveness of a universal, student-focused intervention ('Memory Mates'), specifically focused on supporting students to use attention and working memory strategies within academic contexts, unlike computer-based programs. Memory Mates is presented in the form of icons and explanations, with the strategies embedded within the classroom. Analyses compared the impact of the intervention over 8 months in three schools with three control schools, comprising 13 Year 4 primary school classes. The intervention group students showed a significant improvement in mathematics and spelling; however, there was no differential effect on reading comprehension or academic engagement. Based on the present results, it is contended that implementing Memory Mates within classroom contexts demonstrated promising potential as a new approach to supporting academic progress.